Potential effect of secondary metabolites in Persea americana seeds as an ?-amylase inhibitor on type 2 diabetes mellitus - Anak Agung Bagus Putra Indrakusuma; Luh Putu Sudi Wahyuni; I Gede Wikania Wira Wiguna; Anggi Amanda Triana Devy; I Gede Aswin Parisya Sasmana; Agung Wiwiek Indrayani (Intisari Sains Medis, 2021)
Background: Type 2 diabetes mellitus (T2DM) is a disease that has a high prevalence in the world. The development of plants with medicinal potential is an alternative to control blood sugar levels in T2DM disease, such as avocado (Persea americana). Persea americana seeds contain secondary metabolites that have anti-diabetic activity, but their bioavailability is low.Aim: This study aims to review various secondary metabolites in Persea americana seeds that can reduce blood glucose levels in ?-amylase pathway along with the type of potential encapsulation as a delivery system.Review: Secondary metabolites contained in Persea americana seeds which have activity as anti-diabetic are tannin, quercetin, rutin, kaempferol, saponin, triterpenoid, and alkaloid. Each of them has several mechanisms in diabetes, but their role as ?-amylase inhibitor on T2DM be in focus. There are various types of encapsulation that are known to be able to serve as a delivery system for these secondary metabolites. Those encapsulations are SNEDDS, chitosan-alginate nanoparticle, PLGA nanoparticle, lipid carrier, liposome, and polysaccharide-based enteric-coated nanoparticle. All of them showed good results in improving bioavailability.Conclusion: It is known that various secondary metabolites found in Persea americana seeds influence reducing blood glucose levels notably in the ?-amylase pathway. The low bioavailability of secondary metabolites can be improved by several forms of potential encapsulation. Therefore, herbal substances as adjuvant therapy in T2DM might be a viable management option.